Corruption and Governance Factors as The Determination of The Regional Government Revenue in Indonesia - Yass Andria; Dyah Poespita Ernawati; Yulina Eliza (Universitas Bumigora, 2023)
This study aims to analyze the factors of corruption and governance in determining the amount of Regional Government Revenue in all provinces in Indonesia. This research method uses quantitative approach by analyzing the number of corruption cases that have been taken in kracht in court as well as the results of evaluations of the regional government performance from 2010 to 2017. A total of 30 provinces from 34 provinces in Indonesia were taken as samples to avoid abnormal distribution. The model used is the Fixed Effect Model (FEM) showing that the factors of corruption and governance determine significantly in the opposite direction, where the corruption factor determines the negative direction while the governance factor determines the Regional Government Revenue positively. The two independent variables show that there is a close relationship between corruption and governance, this can occur with improved governance, which will reduce the level of corruption so that it can increase Regional Government Revenue. One way of governance to reduce the occurrence of corruption is to implement the application of one-stop service and e-system.